2023
DOI: 10.31235/osf.io/9mruh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solo Dance? Gender Differences in Housework among Solo Households in the United States

Abstract: This study investigates the gender difference in housework activities among never-married American women and men living solo (one-person households), using 2005-2019 nationally representative data from the American Time Use Survey (ATUS). We find that women in solo households spend more time on housework and old women and men spend more time on it, compared to their younger counterparts. Results also show that education only plays a modest role in time use in solo households, contrary to the negative associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…Starting with young adults living alone, Figure 1 shows a consistently significant gender gap, wherein young adult women who live alone invest more in total housework (12 minutes more) as well as in cleaning (about 7 minutes more) and cooking (about 5 minutes more) than young adult men living alone. These results align with recent work about time use of women and men living alone (Cheng & Sayer, 2023) and offer an essential benchmark for understanding young adults living in shared households. In other words, even when living alone, young adult women spend more time doing housework than young adult men.…”
Section: Gender Gap Across Living Arrangementssupporting
confidence: 85%
See 1 more Smart Citation
“…Starting with young adults living alone, Figure 1 shows a consistently significant gender gap, wherein young adult women who live alone invest more in total housework (12 minutes more) as well as in cleaning (about 7 minutes more) and cooking (about 5 minutes more) than young adult men living alone. These results align with recent work about time use of women and men living alone (Cheng & Sayer, 2023) and offer an essential benchmark for understanding young adults living in shared households. In other words, even when living alone, young adult women spend more time doing housework than young adult men.…”
Section: Gender Gap Across Living Arrangementssupporting
confidence: 85%
“…However, empirical evidence supports a gender hypothesis, even among shared households. In the US, women spend more time than men doing chores such as cleaning, laundry, and cooking, even when they live alone (Cheng & Sayer, 2023;Sayer, 2016). Using the Australian Time Use Survey from 2006, Craig et al (2016) also found gender differences in routine and non-routine housework among young adults living in shared households, alone, or with their parents.…”
Section: The Current Studymentioning
confidence: 96%